Biochemical Response of Maize Plants Grown in the Field Under Different Water Availability: Evaluating the Influence of Leaf Position and Growth Stage - Carina Sá; Etelvina Figueira; Paulo Cardoso (Agronomy)
Drought is a major abiotic stress factor in agriculture and could greatly affect the production of maize, which is a key food source. Understanding the biochemical response of maize throughout the length of the plant and its life cycle when exposed to water deficit is an important step when exploring new agricultural approaches to minimizing crop losses. In this study, maize plants grown in the field were exposed to three different water regimes (100%, 50%, and 0% irrigation). The biochemical status of the top, middle, and basal leaves was assessed at two different stages of their life cycle (vegetative and reproductive) to evaluate how plants respond to different water deficits. The results showed that, in the presence of water stress, maize development was affected and crop production decreased. Antioxidant enzyme activity, oxidative damage, and osmolyte levels were influenced not only by the irrigation levels but also by the plant section sample. Throughout the maize life cycle, lipid peroxidation, ascorbate peroxidase, and starch levels increased in all leaf sections. However, several biochemical responses are specific to the section: top leaves increase their protein carbonylation, superoxide dismutase, and sugar levels; middle leaves increase their proline and sugar levels; and base leaves increase their superoxide dismutase and proline levels throughout the life cycle. These findings suggest that efforts to minimize the damage caused by water deficits in crop production must consider the different plant sections and phases of the maize life cycle.